Pengembangan E-Modul Kimia Berbasis POE (Predict, Observe, Explain) pada Materi Sistem Koloid - Rahman, Baiq Adila Pratiwi; Junaidi, Eka; Hadisaputra, Saprizal (Chemistry Education Practice, 2024)
The purpose of the study is to determine the level of validity and practicality of the POE (Predict, Observe, Explain) based chemistry electronic module on coloid system subject. The study is a Research and Development study which adopts the 4D model (define, design, develop, disseminate). The study population was XI-IPA students of SMAN 5 Mataram in the academic year of 2022/2023 while the sample of this research was 70 students who were taken randomly. The results of the research indeed indicate a very positive outcome. The developed POE (Predict, Observe, Explain) based chemistry electronic module on coloid system subject, has achieved high validity (feasibility) with a score of 0.79 in the valid category. Additionally, the practicality level, as measured by student responses, is very high with a practicality percentage of 84.5%. This leads to the conclusion that the developed e-module is both suitable and practical for use in the learning process. These findings underscore the quality and effectiveness of the e-module in assisting students in gaining a better understanding of chemistry materials.